When Illuminated Manuscripts are not What They Seem: the Cases of the Holkham Bible Picture Book and a Newly Discovered Croatian Altarpiece - Brown, Michelle (IKON, 2008)
Abstract This paper will consider two Christological cycles painted on leaves of vellum during the early fourteenth century. Both series of images are now in the British Library, one set (the Holkham Bible Picture Book) is well known and the other previously obscure; both have been thought to have been designed and painted by manuscript illuminators, because they occur in books. Yet the inclusion of illuminations within books does not necessarily mean that this is the context for which they were originally conceived. The core of the Hokham Bible may have started life as a series of designs for textiles which grew into a book. The second example consists of a series of 24 detached miniatures depicting the ministry and Passion of Christ which, although bound into a book in recent times, were in fact originally nailed to a wooden frame to form a vellum altarpiece – a rare phenomenon. The responses of both artists to the challenges of depicting the narrative of redemption for a wider audience will serve as portals into their age.